2010
DOI: 10.1577/h09-052.1
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of the Pleasure Oyster Crassostrea corteziensis Cultured in Nayarit, Mexico

Abstract: The pleasure oyster Crassostrea corteziensis is collected and cultured in Nayarit on the Pacific coast of Mexico, and the improvement and promotion of its culture are seen as a possible source for the economic development of coastal populations. However, information about the parasite fauna of the pleasure oyster is almost completely lacking. A histopathological survey carried out in two estuaries, Boca del Camichín and Pozo Chino, revealed the presence of hypertrophied gametes, rickettsiales-like prokaryotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
(44 reference statements)
1
12
0
3
Order By: Relevance
“…These organisms can also be found, apart from digestive tubules (primary and secondary, as recorded in the present study) in the epithelium of the intestine and stomach (CÁCERES-MARTÍNEZ et al, 2010), as reported by Sabry et al (2011), who observed changes in the gastric epithelium affected. The results of this study also resemble those found by Boehs et al (2010) in M. guyanensis, with the occurrence of these bacteria in the same anatomical region and low prevalence and degree of infection; and by Pontinha (2009 and Ceuta and Boehs (2012), in C. gigas, C. rhizophorae and M. guyanensis, respectively, with the occurrence of hypertrophy of cells infected by RLOs.…”
Section: Discussionsupporting
confidence: 88%
“…These organisms can also be found, apart from digestive tubules (primary and secondary, as recorded in the present study) in the epithelium of the intestine and stomach (CÁCERES-MARTÍNEZ et al, 2010), as reported by Sabry et al (2011), who observed changes in the gastric epithelium affected. The results of this study also resemble those found by Boehs et al (2010) in M. guyanensis, with the occurrence of these bacteria in the same anatomical region and low prevalence and degree of infection; and by Pontinha (2009 and Ceuta and Boehs (2012), in C. gigas, C. rhizophorae and M. guyanensis, respectively, with the occurrence of hypertrophy of cells infected by RLOs.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest that, when two susceptible host species are present, the progression of the two Perkinsus species can be modified in order to favor parasite progression in the most susceptible oyster species. Despite the knowledge that P. marinus causes outbreaks in C. virginica oysters from the East Coast of the USA (BURRESON & RAGONE-CALVO, 1996), P. marinus was not associated with mortality in other susceptible oyster species (Crassostrea and Saccostrea) (CÁCERES-MARTÍNEZ et al, 2010MOSS et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Production of C. corteziensis now approaches 2000 metric tons/year (Cáceres-Martínez et al, 2010). While there have been some attempts to grow S. palmula (Baqueiro, 1984), culture of this oyster is still nascent and generally co-occurs with that of C. corteziensis.…”
Section: Introductionmentioning
confidence: 99%